2019
DOI: 10.3354/meps12859
|View full text |Cite
|
Sign up to set email alerts
|

A sex-influenced flexible foraging strategy in a tropical seabird, the magnificent frigatebird

Abstract: To successfully exploit resources, animals must be adapted to operate under phenotypic and environmental constraints. The strategies that predators use to locate prey are therefore diverse, particularly for breeding central-place foragers that must balance investment in reproduction and self-maintenance. Magnificent frigatebirds Fregata magnificens are tropical seabirds with intriguing morphology and feeding ecology, which display strikingly unequal levels of parental care (males deserting offspring months bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Blue whales have been shown to adjust their dive behavior based on the density of prey in the area (Goldbogen et al, 2015;Hazen et al, 2015), so it is possible they encountered prey in insufficient concentrations for them to feed upon. More broadly, males and females of central-place foragers are known to have different sex-based foraging strategies arising from different energetic requirements during reproduction and resulting in differential exploitation of the offshore and coastal environment (Breed et al, 2006;Austin et al, 2019). A similar process could be driving the observed differences between male blue and fin whales.…”
Section: Discussionmentioning
confidence: 99%
“…Blue whales have been shown to adjust their dive behavior based on the density of prey in the area (Goldbogen et al, 2015;Hazen et al, 2015), so it is possible they encountered prey in insufficient concentrations for them to feed upon. More broadly, males and females of central-place foragers are known to have different sex-based foraging strategies arising from different energetic requirements during reproduction and resulting in differential exploitation of the offshore and coastal environment (Breed et al, 2006;Austin et al, 2019). A similar process could be driving the observed differences between male blue and fin whales.…”
Section: Discussionmentioning
confidence: 99%
“…1 ; Latitude: 19.663 °N, Longitude: 80.082 °W; estimated population size in 2017: 2094 breeding adults, [ 46 ]); and 2) beach and cliff locations on Cayman Brac that support a small scattered breeding population of BBs (Fig. 1 ; Latitude: 19.711 °N, Longitude: 79.801 °W; estimated population size in 2017: 146 breeding adults, [ 47 ]).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Wintering RCPs must prepare for the ensuing breeding period by balancing the demands of long migratory upand-down flights and self-maintenance while functioning within phenotypic, energetic, and geographical constraints. To meet these challenges, Austin et al (2019) reported that species must adapt their foraging behaviors in ways that ultimately optimize both survival and fitness.…”
Section: Discussionmentioning
confidence: 99%